2015
DOI: 10.1093/jxb/erv480
|View full text |Cite
|
Sign up to set email alerts
|

MutS HOMOLOG1 silencing mediatesORF220substoichiometric shifting and causes male sterility inBrassica juncea

Abstract: Highlight MSH1 participates in fertility reversion and male sterility by mediating mitochondrial genomic substoichiometric shifting of ORF220 and altering expression of anther development-associated genes in Brassica juncea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 48 publications
(69 reference statements)
0
32
0
Order By: Relevance
“…Moreover, altered activity of MSH1 in Brassica juncea is correlated to the substoichiometric shifting of the CMS-associated ORF220. Notably, increased ORF220 copy number was found in male sterile RNAi-MSH1 lines, which provides a new approach to manipulate CMS for agronomic use (ZHAO et al 2015).…”
Section: "Recombination Surveillance" Mutantsmentioning
confidence: 99%
“…Moreover, altered activity of MSH1 in Brassica juncea is correlated to the substoichiometric shifting of the CMS-associated ORF220. Notably, increased ORF220 copy number was found in male sterile RNAi-MSH1 lines, which provides a new approach to manipulate CMS for agronomic use (ZHAO et al 2015).…”
Section: "Recombination Surveillance" Mutantsmentioning
confidence: 99%
“…It is reported that the other members of MSH2 family function beyond MMR. MSH1 is required for mitochondrial stability (Reenan & Kolodner, ) and disruption of MSH1 can influence male sterility in several species (Sandhu, Abdelnoor, & Mackenzie, ; Zhao et al., ). The MSH4 and MSH5 form heterodimer between them without involving MSH2 and exclusively function in meiosis (Hollingsworth, Ponte, & Halsey, ; Lu et al., ; Schofield & Hsieh, ; Wang et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The orf108 gene is also associated with CMS in the cytoplasm of Moricandia arvensis ( Ashutosh et al , 2008 ; Kumar et al , 2012 ). A chimeric orf220 gene from CMS B. juncea (stem mustard) causes male sterility ( Yang et al , 2010 ) and MSH1-RNAi from spontaneous fertile-revertant lines was found to increase the orf220 copy number and induce male sterility ( Zhao et al , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of mitochondrial genes and those involved early anther development (e.g. WUS , SPL , AP3 , PI , DYT1 , and AMS ) were found to be down-regulated in male-sterility lines ( Yang et al , 2010 ; Zhao et al , 2016 ).…”
Section: Introductionmentioning
confidence: 99%